Smoothing The Flow of Money - Wang Jun (Beijing review, 2016)
China＇s investment and financing systems will be overhauled in the hope of ensuring stable economic growth,adjusting the economic structure and improving people＇s livelihoods. A new guideline outlining the reform measures was issued by the Central Committee of the Communist Party of China （CPC） and the State Council on July 18.